Newbouldia laevis (Bignoniaceae) and Zanthoxylum zanthoxyloides (Rutaceae) used in folk medicine: anatomical features, preliminary phytochemical analysis and anthelmintic activity - OLOUNLADE, ABIODOUN PASCAL; Azando, Erick Virgile Bertrand; AKOUEDEGNI, COOVI GUENOLE; HOUNZANGBE ADOTE, SYLVIE ELIANE GHISLAINE (My University, 2016)
Newbouldia laevis (P. Beauv.) Seeman ex Bureau is a Bignoniaceae widely distributed in USA, Central Africa and West Africa. Zanthoxylum zanthoxyloides (Lam.) Zepernick & Timler is a Rutaceae widely distributed in West Africa. They have been commonly used in folk medicines against human and animal external and gastrointestinal parasites. In this study, the botanical identification criteria as well as a preliminary phytochemical composition and an anthelmintic activity of these species are reported. Extracts of both plants were prepared by use of chloroform, acetone/water (70:30), ethanol/water (70:30) and their anthelmintic activity was measured by the larval migration inhibition assay (LMI) applied on the abomasale species H. contortus. Then anatomical and phytochemical examinations were performed. Anatomical study has shown that N. laevis presents: lower epidermis with sinuous wall-cells and anomocytic stomata, acicular calcium oxalate crystals, unicellular echinulate covering trichomes, 8-20 cell-head glandular trichomes. Anatomical study has shown that the leaflet of Z. zanthoxyloides presents as anatomic features: epidermis with polygonal-cells and wavy striated cuticle, calcium oxalate clusters and sphaerocrystalline masses of flavonoid compounds. The phytochemical screening revealed the presence of flavonoids, tannins, alkaloids, volatile oil, anthocyanins, leucoanthocyanins, reducing compounds and coumarins in the leaves of the studied species. Saponins, cyanogenic and cardiac glycosides were absent in all the studied plants parts. Mucilages were present in Zanthoxylum zanthoxyloides while quinones were present in Newbouldia laevis. Chloroform, acetone and ethanol extracts were used for anthelmintic studies. The extracts of N. laevis and Z. zanthoxyloides inhibit in vitro the larval migration of H. contortus. This effect is dose depending (p < 0,001). Acetonic extracts seem to be more active especially in high doses. These extracts from N. laevis and Z. zanthoxyloides, identified in the ethno knowledge could be used as improved traditional medicines and may contain compounds with potential anthelmintic activity.
Keywords: Small ruminants; phytochemical; Haemonchus contortus; extracts of plants; Newbouldia laevis; Zanthoxylum Zanthoxyloides; Benin